Clerodane diterpenoids from an edible plant Justicia insularis: discovery, cytotoxicity, and apoptosis induction in human ovarian cancer cells - Fadayomi, IE; Johnson-Ajinwo, OR; Pires, E; McCullagh, J; Claridge, TDW; Forsyth, NR; Li, W-W (MDPI, 2021)
Objectives: The toxicity of chemotherapeutic anticancer drugs is a serious issue in clinics. Drug discovery from edible and medicinal plants represents a promising approach towards finding safer anticancer therapeutics. Justicia insularis T. Anderson (Acanthaceae) is an edible and medicinal plant in Nigeria. This study aims to discover cytotoxic compounds from this rarely explored J. insularis and investigate their underlying mechanism of action. Methods: The cytotoxicity of the plant extract was evaluated in human ovarian cancer cell lines and normal human ovarian surface epithelia (HOE) cells using a sulforhodamine B assay. Bioassay-guided isolation was carried out using column chromatography including HPLC, and the isolated natural products were characterized using GC-MS, LC-HRMS, and 1D/2D NMR techniques. Induction of apoptosis was evaluated using Caspase 3/7, 8, and 9, and Annexin V and PI based flow cytometry assays. SwissADME and SwissTargetPrediction web tools were used to predict the molecular properties and possible protein targets of identified active compounds. Key finding: The two cytotoxic compounds were identified as clerodane diterpenoids: 16(α/β)-hydroxy-cleroda-3,13(14)Z-dien-15,16-olide (1) and 16-oxo-cleroda-3,13(14)E-dien-15-oic acid (2) from the Acanthaceous plant for the first time. Compound 1 was a very abundant compound (0.7% per dry weight of plant material) and was shown to be more potent than compound 2 with IC50 values in the micromolar range against OVCAR-4 and OVCAR-8 cancer cells. Compounds 1 and 2 were less cytotoxic to HOE cell line. Both compounds induced apoptosis by increasing caspase 3/7 activities in a concentration dependent manner. Compound 1 further increased caspase 8 and 9 activities and apoptosis cell populations. Compounds 1 and 2 are both drug like, and compound 1 may target various proteins including a kinase. Conclusions: Clerodane diterpenoids (1 and 2) in J. insularis were identified as cytotoxic to ovarian cancer cells via the induction of apoptosis, providing an abundant and valuable source of hit compounds for the treatment of ovarian cancer.